Morphological diversity and cluster relationships of indigenous Musa spp. based on biosystematic in North Maluku, Indonesia - SUPARMAN SUPARMAN; M. NASIR TAMALENE; BAHTIAR BAHTIAR; ZAHROBATUL LIL ILMI (Society for Indonesian Biodiversity, 2025)
Abstract. Suparman S, Tamalene MN, Bahtiar B, Ilmi ZL. 2025. Morphological diversity and cluster relationships of indigenous Musa spp. based on biosystematic in North Maluku, Indonesia. Biodiversitas 26: 4220-4228. The banana (Musa spp.) is a culturally and economically vital crop in North Maluku, yet its local morphological diversity remains underdocumented. This study examined 40 indigenous banana cultivars from five islands (Morotai, Halmahera, Ternate, Tidore, Bacan) using 52 standardized morphological descriptors. Genomic groups were inferred morphologically (AA/AAA, AAB, ABB, AB). Phenetic relationships were analyzed via Principal Component Analysis (PCA) and UPGMA clustering using Euclidean and Ward's methods. Four distinct clusters were identified, i.e., group A (penganten), group B (tanduk), group C (takoapi), and group D (mas); the clusters were independent of genomic classification. Genome group distribution included AA/AAA (52.5%), AAB (32.5%), ABB (12.5%), and AB (2.5%). Key traits differentiating clusters included petiole canal morphology, bract coloration, and fruit shape. Most cultivars (75%) were distributed below 100 masl, showcasing their ecological adaptability. A few (e.g., Sarango, Goroho Putih) were found at elevations >150 m, indicating ecological adaptability. The incongruence between morphological clusters and genomic groups suggests the influence of somaclonal variation, ecological adaptation, and cultural selection. These findings provide a crucial baseline for in situ conservation and targeted breeding of regionally adapted banana germplasm in eastern Indonesia. Conservation efforts are especially critical for cultivars possessing rare genome types, given their vulnerability and genetic significance.